PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT DUTA MULTI KARYA - Novita, Livia; M. Khoiri (LPPM Universitas Putera Batam, 2022)
The purpose of this study was to determine whether training and work discipline affect work productivity at PT Duta Multi Karya. The research was conducted using quantitative techniques. The population used consisted of 130 employees of PT Duta Multi Karya. 130 employees of PT Duta Multi Karya were used as research samples using the saturated sampling method. Questionnaires were used as a data collection technique. By using SPSS 25 software, data analysis techniques include descriptive statistical tests, data quality tests, classical assumption tests, influence tests, and hypothesis testing. Based on the results of multiple linear regression, training has an effect of 0.208 or 20.8% on work productivity (Y) at PT Duta Multi Karya and work discipline (X2) has an effect of 0.447 or 44.7% on work productivity (Y) at PT Duta Multi Works. The factor of training and work discipline has an effect on work productivity (Y) at PT Duta Multi Karya by 82.1%.8% according to the data of the coefficient of determination (R2). Based on the results of the t test, training has a partially significant effect on work productivity and work discipline has a partially significant effect on work productivity, and the f test results show that training and work discipline simultaneously have a significant effect on work productivity (Y) at PT Duta Multi Karya